Avaliação de modelos matemáticos para a simulação do escoamento água – ar na flotação por ar dissolvido utilizando fluidodinâmica computacional - Rodrigues, João Paulo (2018)
The concern with the future of water on the planet has increased in past years, mainly due to the recent water crisis suffered throughout the country. The dissolved air flotation (DAF) operation is an example of the resumption of studies in the application and optimization of classic industry operations and has its potential for water treatment confirmed in the literature. It is characterized by using air microbubbles for the removal of suspended particles in liquid mixtures and has already been presented as an useful operation for treatment steps, however, with a high operating cost. In the study of flows in equipment, the Computational Fluid Dynamic (CFD) technique has been highlighted. This technique can aid in analyzing and obtaining information on constructive equipment configurations, scaling parameters and optimized operating conditions. In this work, the Ansys Fluent 14.5 software was used for the CFD simulation of the DAF process in horizontal tank, seeking to fit a representative mathematical model (set of equations) and numerical procedure based on experimental data from the literature. Initially, for the definition of the computational mesh, the GCI test was applied, capable of quantifying the mesh discretization error. Then, different multiphase models that consider the Euler-Euler approach were compared through the qualitative behavior for the diameters of 30-50-70 μm. With the diameter of 50 μm, the influence of the turbulence, trawling and contour conditions for the tank surface used by the literature to represent the FAD process was verified. After adjusting the fluid dynamics model, the population balance equations (EBP) for the microbubble size distribution was applied and the influence of models describing the phenomena interaction like coalescence (turbulent and Luo model) and breakage (Luo model) in the structure of the air flow and air distribution was verified. A greater influence of the coalescence phenomenon was observed.